No consequences: an analysis of images and impression management on Facebook - Pennington, Natalie R.D. (Kansas State University, 2010)
Goffman (1959) suggests that it is through communication that we are able to form impressions of self and express our identity to society. With the emergence of computer-mediated communication and social network sites we’ve witnessed a new form of communication online, and as a result, the traditional forms of impression management used to construct and display identity have shifted to include not just speaking or writing our identity, but displaying who we are through photographs online. This research investigates the connection between the use of a particular social network site, Facebook, and the pattern of impression management techniques through the management and addition of photographs on the site. A two-month ethnography of 16 participants was conducted followed by 3 interviews. Results indicate that digital natives (individuals who have grown up heavily in the presence of technology) tend to convey a variety of conflicting online identities through images, resulting in a “no consequences” generation that, while concerned with privacy, are more concerned with communicating an impression that fits within their primary social roles.
Keywords: Facebook; Visual communication; Computer-mediated Communication; Impression management; Speech Communication (0459)